The Role of Organizational Commitment in Mediating Perceived Organizational Support on Organizational Citizenship Behavior - Ramadhani, Jasmine Salwa; Rini, Hesty Prima; Evanthi, Ayundha (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study aims to empirically examine the influence of Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB) with Organizational Commitment (OC) serving as a mediating variable at PT SBC Berkah Bersama. The research employs a quantitative approach using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method for data analysis. The sample consists of 70 front-line employees selected through non-probability sampling with a saturated sampling technique. The findings reveal that POS has a positive and significant effect on both OCB and Organizational Commitment. Furthermore, Organizational Commitment also exerts a positive influence on OCB. The mediation analysis indicates that Organizational Commitment significantly mediates the relationship between POS and OCB, demonstrating a partial mediation effect. This finding suggests that optimal organizational support can enhance employee commitment, which in turn encourages voluntary behavior beyond their formal roles. This study has practical implications for the management of PT SBC Berkah Bersama to strengthen organizational support strategies as an effort to enhance employee loyalty and extra-role behavior.